Proposed mechanisms for coincidence detection in the auditory brainstem - Maršálek, Petr; Lánský, Petr (Biological cybernetics, 2005)
Sound localization in mammals uses two distinct neural circuits, one for low- and one for high-frequency bands. Recent experiments call for revision of the theory explaining how the direction of incoming sound is calculated. We propose such a revised theory. Our theory is based on probabilistic spiking and probabilistic delay of spikes from both sides. We have applied the mechanism originally proposed as an operation on spike trains resulting in multiplication of firing rates. We have adapted this mechanism for the case of synchronous spike trains. The mechanism has to detect spikes from both sides within a short time window. Therefore, in both circuits neurons act as coincidence detectors. In the excitatory low-frequency circuit we call the mechanism the excitatory coincidence detection, to distinguish it from the mechanism of the inhibitory coincidence detection in the high-frequency circuit. The times to first spike and gains of the two mechanisms are calculated. We show how the output gains of the mechanisms predict the dip within the human frequency sensitivity range. This dip has been described in human psychophysical experiments.
Keywords: akustická stimulace; finanční podpora výzkumu jako téma; Auditory Perception; modely neurologické; sluchová percepce; Research Support as Topic; Acoustic Stimulation; mozkový kmen; Brain Stem; Models, Neurological